(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The term "women empowerment" has gained widespread recognition in the twenty-first century. Women's empowerment encompasses a variety of factors, including economic possibilities, societal justice, & personal rights. Female's emancipation on its own explains how various privileges, including social and political rights and economic and legal equality, should also apply equally to women. We owe women all of these privileges. But nearly all around in the world, women and girls remain to be deprived of these basic rights. , frequently for no other reason than their gender. Since ancient times, men have held women in inferior and subordinate positions. Women's empowerment is among the most pressing issues today and a necessity, yet the reality is that things are not satisfactory enough. Gender mainstreaming accelerates the process of achieving strengthening women and advancing gendered equality, which is the ultimate objective. The Indian government has developed programs and policies at various stages to address various areas and tactics of gender advancement in this approach. Womens upliftment and empowerment is still necessary. In this essay, an endeavour has been undertaken to shed some light on the various problems and difficulties experienced by Indian women. A few recommendations are also made for women's empowerment in the conclusion.